METHODOLOGY OF DETERMINING THE SIZE AND EXCHANGEABILITY OF CONTAINERS AT TERMINALS - Ivaković, Čedomir (Promet - Traffic&Transportation)
The paper analyzes the methodology of determining thesize of containers and their exchangeability in a terminal. Thesize of containers affects the exchangeability as well as the averageusability of capacity and the lack of uniformity in the deliveryof cargo suitable for container transport. These assumptionsdefine the size of the depot, the lengths and widths of theroad and railway tracks and manipulation areas, and also thenumber and size of shipping quays. Apart from these elementsthe static and dynamic capacity of the terminal depend also onthe handling equipment.